A DIALOGUE ON PATRIARCHY FROM THE FEMINISTIC PERSPECTIVE - Saxena, Puja; Joshi, Vishal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Several feminist ideologies have placed a strong emphasis on the idea of patriarchy. It is an attempt to provide an explanation for the gender-based distribution of privilege and power that is evident from a variety of objective metrics. According to the patriarchs of ancient Greece, a patriarchy was a system of government in which the older men held and shared authority. When sociologists and historians of today refer to a "patriarchal society," They indicate that men are more likely to be in positions of authority and privilege, such as head of state, head of family, and leaders of social groupings. There is a hierarchy among men in patriarchy as well. In a typical patriarchal society, the older males ruled over the younger men. Under the contemporary patriarchal system, certain males are deemed more powerful due to their authority, and this power structure is accepted. The male gender dominates. Added to the fact that women are viewed as inferior by men, they have also experienced assault, oppression, exploitation, humiliation, and dominance. For the purpose of evaluating Indian women now, a brief history of Indian women's cultural origins is necessary. Indian women are part of a deeply ingrained civilization. A rather solid social framework that has developed over a millennium is responsible for instilling patterns in her behaviour, which may manifest as a certain belief or style of acting. Consequently, a complete grasp of India is necessary in order to define cultural practices and depictions of women as well as comprehend the current state of affairs for Indian women. Thus, this essay aims to analyse women's identities and the patriarchal structure of Indian society. Though they have made great strides in all spheres of life, women in contemporary India still have to contend with pervasive patriarchal mind-sets.